57. ASSESSMENT OF OVERALL SURVIVAL FOLLOWING TRANSURETHRAL RESECTION FOR ADVANCED-STAGE PROSTATE CANCER COMBINED WITH BILATERAL ORCHIECTOMY: A RETROSPECTIVE STUDY AT VIET DUC HOSPITAL FROM JANUARY 2018 TO DECEMBER 2022 (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the overall survival time following transurethral resection for advanced stage prostate cancer combined with bilateral orchiectomy at Viet Duc University Hospital from January 2018 to December 2022.Research methods: The retrospective followed up longitudinally on 217 patients diagnosed with advanced prostate cancer who underwent transurethral resection of the tumor with bilateral orchiectomy.Results: There were 99 patients who died, accounting for 45.6%. The survival rate decreased gradually over the follow-up time in the groups from 24 to 72 months after surgery, corresponding to 67.1% to 36.8%. The main cause of death was cancer metastasis to other organs. Factors affecting survival rate and overall survival time were Gleason score, age group and stage of Prostate cancer (p < 0.05). The average survival time of all patients studied was 45.4 months and 50% of patients survived 49 months. The average survival time of deceased patients was 22.41 ± 14.3 (months) with the shortest being 1 month and the longest being 62 months.Conclusion: There was a correlation between survival rate and overall survival time with Gleason score, advanced age and prostate cancer stage. The average survival time of all study patients was 45.4 months, and that of deceased patients was 22.41 ± 14.3 (months).
Keywords: Prostate cancer, post-operative results, median survival time.